Corrosion prevention of steel frames on an iconic villa by zinc galvanic anode - Hallopeau Xavier; Lesieutre Olivier; Marie-Victoire Elisabeth; Bouichou Myriam (MATEC Web of Conferences, 2025)
The renovation of a French building classified as an historic monument must meet specific requirements, in particular very precise rules within the framework of the scientific and technical control. The Villa Ephrussi de Rothschild, one of the most beautiful Renaissance-style palaces on the Côte d’Azur, was built on a summit of the St Jean Cap Ferrat peninsula between 1905 and 1912. During the restoration of the east and north facades, it was discovered that the corners of the monumental staircase were covered with an I-shaped metal frame made up of riveted angles and plates. Its advanced state of deterioration made it necessary to reconsider the initial maintenance strategy. In this context, this article discusses the results of its implementation through the partial application of an epoxy coating on the steel frame structure and to the installation of long zinc sacrificial anodes for cathodic protection.